Intracellular probes for imaging oxygen concentration: how good are they?. (21st April 2015) - Dmitriev, Ruslan I; Papkovsky, Dmitri B
Abstract: In the last decade a number of cell-permeable phosphorescence based probes for imaging of (intra)cellular oxygen (icO2 ) have been described. These small molecule, supramolecular and nanoparticle structures, although allowing analysis of hypoxia, local gradients and fluctuations in O2, responses to stimulation and drug treatment at sub-cellular level with high spatial and temporal resolution, differ significantly in their operational performance and applicability to different cell and tissue models. Here we discuss and compare these probes with respect to their staining efficiency, brightness, photostability, toxicity, cell specificity, compatibility with different cell and tissue models, and analytical performance. Merits and limitations of particular probes are highlighted and strategies for development of new high-performance O2 imaging probes defined. Key application areas in hypoxia research, stem cells, cancer biology and tissue physiology are also discussed.